Re-Sacralising Architectural Pedagogy: A Tawhidic Framework for the Digital Age. - Salam, Hailane; Mohd For, Liyana Mahfuzah; Samadi, Zalina; Jimi Sham, Rashidah (Journal of Islamic, Social, Economics and Development, 2025)
Contemporary architectural education in Muslim societies often mirrors technocratic global models, emphasising technical production while neglecting spiritual and symbolic dimensions. This paper proposes a tawhidic pedagogical framework that reorients Islamic architectural education toward the Qur’anic principle of tawhid (Divine Unity) while adapting to digital and hybrid learning contexts. Drawing on the spiritual cosmology of traditional Malay architecture—particularly the Masjid Kampung Laut—the framework integrates ʿilm (knowledge), adab (discipline), and maʿrifah (spiritual insight) with digital tools such as virtual heritage walkthroughs, symbolic mapping, and reflective e-journals. Findings from case studies and digital classroom applications reveal that embedding digital pedagogy in a tawhidic worldview not only preserves sacred meaning but also fosters ethical, contemplative, and spiritually conscious design practice. By merging Islamic epistemology with digital innovation, this study contributes to the decolonisation of architectural education, sustains sacred heritage, and positions the digital classroom as a new mihrab—orienting learners toward the Divine through contemporary platforms.